Family solidarity in the face of stress: responses to drug use problems in Greece. (4th July 2017) - Fotopoulou, Maria; Parkes, Tessa
Abstract: Background: In the past, Greek drug-affected families had predominantly been conceptualized as one of the main causes of drug problems. This study explored the ways drug-affected families respond to, and cope with, a relative's drug problem by examining the perceptions of both Greek drug users and drug-affected families. Method: A qualitative study comprised of semi-structured in-depth interviews was conducted in two state drug agencies in Thessaloniki, Greece. A total of 40 adult problem drug-using men and women and eight parents of problem drug users were asked to reflect on the ways families respond to, and cope with, drug use. The method of data analysis involved a manual systematic identification of themes in participant narratives in line with analytic induction principles. Results: After discovery of the drug problem, all families were reported as coping with their adult children's drug problems in ways consistent with the stress-strain-coping-support model. The emergent high engagement and low withdrawal coping exhibited by study participants can be contextualized by situating these strategies within the Greek cultural milieu and the notion of familism. While the data illustrate the importance of family solidarity in the face of addiction, caution is invited in making generalizations as sample selection may provide an alternative explanation for study findings. Conclusion: The paper advocates for a non-pathological view of drug-affected families and highlights the importance of cultural context. The stress-strain-coping-support model helps to depathologise and better understand family reactions to problem drug use. Implications for non-stigmatizing and culturally relevant policy and practice are outlined.